Importance of Placing Gore-Tex in the Subperiosteal Plane for Augmentation Rhinoplasty - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Objective: The purpose of this study was to present the placement technique of Gore-Tex implants for nasal augmentation. Methods: The study group comprised 32 patients of various nasal deformities who underwent consecutive rhinoplasty via open approach with Gore-Tex implant material for dorsal augmentation. A pocket is made subperiostally at the nasal dorsum. The implant is rinsed in antibiotic solution and placed in position. Complications due to Gore-Tex were observed during the follow-up period. Results: There were 12 men and 20 women. The mean age was 28.4 years. There were 9 primary rhinoplasty and 23 revision rhinoplasty. Patients were followed up postoperatively for 12 to 24 months. During the postoperative follow-up period, no complications were encountered in this series of patients. The implants were stable and immobile under the skin. Conclusions: In the cases of nasal dorsum augmentation, Gore-Tex can be a suitable graft material. We recommend implanting graft materials at subperiosteal plane to provide better stabilization and low complication rates.
Keywords: Rhinoplasty; Gore-Tex; subperiosteal; augmentation; POROUS POLYETHYLENE IMPLANTS; EXPANDED POLYTETRAFLUOROETHYLENE; NASAL RECONSTRUCTION; DORSAL AUGMENTATION; 6-YEAR EXPERIENCE